Constructing the Ideal Model of Local Government Guidance and Control Effectiveness in Indonesia - Hadi Prabowo (Institut Pemerintahan Dalam Negeri (IPDN), 2019)
This research aims to examine and analyze the effect of implementing guidance andcontrolling policies on the effectiveness of the implementation of local autonomy inIndonesia. The research method used is the two stages mixed method with a quantitativeapproach first followed by a qualitative approach. At the quantitative method stage, thisstudy uses regression analysis, and the qualitative approach utilizes ASOCA methodanalysis (Ability, Strength, Opportunities, Culture, and Agility). The population used inthis study is all autonomous regions in Indonesia as many as 542 regions. The studysample was 85 regions using simple random sampling technique and grouped in 5 regionsbased on geographical approach and stratified random sampling, which consisted of 5provinces, 65 regencies and 15 cities. Quantitative data collection is done throughquestionnaires with respondents as many as 10 people while qualitative data is collectedthrough interviews and focus group discussions (FGD). This study obtained severalimportant findings. Firstly, implementation of policy showed a significant influence on theeffectiveness of the implementation of local autonomy. Thus, better policy implementtionwill generate the local autonomy more effective. Secondly, guidance and controllingshows a significant influence on the effectiveness of the implementation of localautonomy. Thus, enhanced the guidance and controlling will cause the local autonomymore effective. Thirdly, the implementation of guidance and controlling policies togethershows a significant influence on the effectiveness of the implementation of local autonomy.Thus, better implementation of guidance and controlling policies will make localautonomy more effective. And lastly, based on qualitative analysis, it was obtainedreinforcement of the results of quantitative analysis that proved the influence of variableX1, variable X2 with variable Y, and even found a new model for implementation ofguidance and controlling policies on the effectiveness of implementing local autonomy byapplying the HADI model (Human resources, Acceptance, Development, and Innovation)as an alternative model of fostering and monitoring the implementation of localgovernment.